Kontribusi SLB Dalam Memenuhi Kebutuhan Wajib Belajar Anak Berkebutuhan Khusus Di SLB Budi Nurani Kota Sukabumi - Ujang Natadireja; Siti Qomariyah; Rubi Babullah; Najrul Jimatul Rizki (LPPM Politeknik Pratama, 2023)
The preamble to the 1945 Constitution confirms that one of the goals of the state is to educate the life of the nation. This is relevant to article 31 of the 1945 Constitution on education which states that every citizen has the right to be taught. In this case the government is responsible for progress in national education. As human beings, children with special needs have the right to grow and develop in the midst of family, society and nation. He has the right to go to school just like any other brother who has no abnormalities or is normal. Allah Almighty has the noble intention that parents have children with special needs, and people must believe in this by obeying Him. To get to know more about the school of children with special needs (ABK), the author conducted a small study in a school in which specifically were ABK students. The school is called Sekolah Luar Biasa (SLB) A Budi Nurani and is located on Jl. Lio Balandongan Complex Propelat number 169 Sudajaya hilir district Baros sukabumi city, West Java Indonesia. The method used in this research is a descriptive qualitative method. Where researchers test the validity of the data by triangulation of sources, namely by conducting interviews with principals and educators and educators which were carried out on April 7, 2022 and followed up with periodic communication. The findings of researchers, in addition to gaining extraordinary experience, the author learned various lessons beyond the usual ones. Where not all humans are created intact and normal as usual, and the ways and learning processes are different and vary according to the conditions of the students. Within its limitations, every human being has advantages in other fields.